Biomaterial spider silk: Potential candidate for airbag fabric material. Issue 1 (15th March 2018) - Prajapati, Kaushik Govindbhai; Patil, Sandeep P.; Carmai, Julaluk; Koetniyom, Saiprasit; Markert, Bernd
Abstract: In the present work, the mechanical properties of spider silk are assigned to the airbag fabric material. Finite element simulations were performed on the airbag model in order to study its benefits over the traditional fabric material. We designed the airbag model with spider silk material and performed impact analysis. Finally, the obtained results are compared with the standard airbag test. Our analysis pave the way towards the new promising material for airbags. (© 2017 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)